Array Genotyping of Transfusion Relevant Blood Cell Antigens in 6946 Ancestrally Diverse Subjects - Gleadall, Nicholas S; Koets, Lianne; Shamardina, Olga; Gollub, Jeremy; Gottschalk, Aaron J; Razeghi, Orod; Ochoa, Gorka; Stephens, Jonathan; Varma, Ram; Martin, Jennifer; Allara, Elias; Brown, Colin J; et al. (Blood, 2025)
Blood transfusions save millions of lives worldwide each year, yet formation of antibodies against non-self antigens remains a significant problem, particularly in frequently transfused patients. We designed and tested the Universal Blood Donor Typing (UBDT_PC1) array for automated high-throughput simultaneous typing of human erythroid, platelet, leukocyte, and neutrophil antigens (HEA, HPA, HLA, and HNA, respectively) to support selection of blood products matched beyond ABO/Rh. Typing samples from 6946 donors of European, African, Admixed American, South Asian, and East Asian ancestry at two different laboratories showed a genotype reproducibility of ≥99% for 17 244 variants, translating to 99.98%, 99.90%, and 99.93% concordance across 338 372 HEA, 53 270 HPA, and 107 094 HLA genotypes, respectively. Compared to previous clinical typing data, concordance was 99.9% and 99.6% for 245 874 HEA and 3726 HPA comparisons, respectively. HLA types were 99.1% concordant with clinical typing across 8130 comparisons, with imputation accuracy higher in Europeans versus non-Europeans. Seven variant RHD alleles, a GYPB deletion underlying the U− phenotype, and 14 high-frequency antigen negative types were also detected. Beyond blood typing, hereditary hemochromatosis-associated HFE variants were identified in 276 donors. We found that the UBDT_PC1 array can reliably type a wide range of blood cell antigens across diverse ancestries. Reproducibility and accuracy were retained when transfusion-relevant targets from the UBDT_PC1 array were incorporated into the UKBB_v2.2 genome-wide typing array. The results represent the potential for significant advancement towards improved patient care by reducing harm in transfused patients through extended matching.